Young Adult Perspectives on a Successful Transition from Pediatric to Adult Care in Sickle Cell Disease - Sobota, Amy E.; Umeh, Emeka; Mack, Jennifer W. (Journal of Hematology Research, 2015)
Objective: This qualitative study sought to learn from young adults with sickle cell disease (SCD) about their experience leaving pediatric care and perspective on what makes a successful transition. Methods: Fifteen young adults with SCD who had left pediatric care within the previous five years participated in focus groups led by a trained moderator. Transcripts were analyzed using grounded theory. Results: Four main themes emerged from the analysis: facilitators of transition (meeting the adult provider prior to transfer, knowing what to expect, gradually taking over disease self-management and starting the process early), barriers to transition (negative perceived attitude of adult staff, lack of SCD specific knowledge by both patients and staff, and competing priorities interfering with transition preparation), what young adults wished for in a transition program (opportunities to meet more staff prior to transfer, more information about the differences between pediatric and adult care, learning from a peer who has been through the process, more SCD teaching, and flexibility in transition preparation) and how they define a successful transition (gradually assuming responsibility for self-management of their SCD). Conclusion: Our findings present unique opportunities to learn from young adults with SCD about ways to improve current transition programs.